Digital Content Marketing for Promoting Creative Economy at Dharmawangsa Entrepreneur Community (DEC) - Gustiana, Zelvi; Firah, Al; Elyas, Ananda Hadi (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 18 Nomor 2 Tahun 2024DO - 10.24843/MATRIK:JMBK.2024.v18.i02.p02, 2024)
As technology advances, digital content marketing becomes crucial for Micro, Small, and Medium Enterprises (MSMEs) like the Dharmawangsa Entrepreneur Community (DEC), which face challenges in adopting new marketing strategies. This study explores the integration of both conventional and digital marketing methods by DEC members to enhance their competitiveness. Using a mixed-methods approach, data were collected through purposive sampling involving interviews and questionnaires. Findings indicate that while DEC members predominantly use traditional methods such as bazaars, 20% engage in digital marketing, utilizing platforms like Canva, WhatsApp, Instagram, and TikTok. Key sectors include food & beverage (56.7%) and creative industries, with women comprising 60% of the community. The main challenges identified were limited digital skills and reliance on traditional approaches. The study concludes that targeted training and mentorship programs are essential to foster greater digital adoption among MSMEs, ultimately enhancing visibility and business performance. Keyword : creative economy; digital content marketing; promotional media